Automated Fog Node Audit and Certification Scheme With Multiple Attestation Certificate Authorities - Shuaib Anath; Tahmid Quazi; Bashan Naidoo (IEEE Access)
Fog computing is a complementary paradigm to cloud computing. It aims to improve the performance of Internet of Things (IoT) applications by positioning fog computing nodes closer to IoT networks. Establishing trust between fog nodes and cloud service providers is challenging because fog providers are typically third parties. The automated Fog Node Audit and Certification (FoNAC) scheme is a solution for establishing cloud trust in fog nodes. A key component for fog node trust establishment in the scheme is the attestation key certificate issued by an attestation Certificate Authority (CA). The FoNAC scheme assumes that the attestation CA certification service is readily available. However, this is a strong assumption that requires further study. Therefore, this paper aims to investigate the service availability of the attestation CA in the FoNAC scheme. This study examines the CA service availability in the FoNAC scheme, revealing that a single centralized attestation CA leads to a single point of failure that disables FoNAC and causes service bottlenecks. This paper proposes a distributed multiple attestation CA system to overcome these limitations. The certification service availability of the system is investigated as a finite-queue queuing system. Results demonstrate that increasing the number of CAs significantly increases service availability, achieving 93% availability with three CAs versus 42% with one CA at 500 requests per second. The distributed nature of the proposed system overcomes the limitation of a single point of failure, and the results show that multiple CAs increase the availability of the certification service, thereby reducing bottlenecks.